Tingkatan Kebutuhan Yossarian dalam Novel Catch-22 Karya Joseph Heller - Maya Kurnia Dewi (Faculty of Economics, Law, and Humanities, 2020)
TThe theory of hierarchy of needs developed by Abraham Harold Maslow consists offve levels of needs, namely at the lowest level of physiological needs, the second levelof safety needs, the third level of love and belonging needs, the fourth level of esteemneeds and the highest need is the need for self-actualization. Maslow describes humansas creatures that have never been in a state of satisfaction. If a need has been satisfed,then other needs will appear demanding satisfaction, and so on. This study analyzes themain character, Yossarian, in Joseph Heller's Catch-22 novel, which is then related tothe hierarchy of Yossarian needs. From the results of the analysis it can be seen thatphysiological needs can be met properly, while the needs for safety are not at all obtainedby Yossarian. As a result of not meeting the needs of the second level, the needs of thethird to ffth level cannot be fulflled properly